An electron microscopic characterization method for microscopic study of micro / nanomaterial-liquid interface
Through liquid nitrogen low-temperature rapid freezing and freeze-drying technology, combined with analytical electron microscope, the problem of high requirements for micro/nanomaterial-liquid interface research equipment and sample preparation in the prior art is solved, and efficient analysis and three-dimensional reconstruction of the interface at room temperature are achieved.
Patent Information
- Application Number
- CN202411169878.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-26
AI Technical Summary
When studying the micro/nanomaterial-liquid interface, the existing electron microscope characterization methods have high requirements for equipment and sample preparation, long operating time and limited economic benefits, and cannot effectively analyze the interface at room temperature.
The liquid nitrogen low-temperature rapid freezing technology is used to freeze the liquid layer of the micro/nanomaterial-liquid interface in situ, and then the liquid layer is retained by freeze drying, and characterized in combination with analytical electron microscope to achieve efficient analysis of the micro/nanomaterial-liquid interface and its interactions at room temperature.
Overcoming the limitation that electron microscope can only image in low temperature environments, it realizes clear imaging and three-dimensional reconstruction of the micro/nanomaterial-liquid interface at room temperature, and improves research efficiency and applicability.
Smart Images

Figure CN118671386B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid-liquid interface microscopic research methods, specifically to an electron microscope characterization method for microscopic research of micro / nano material-liquid interfaces, and more particularly to a sample preparation and characterization method based on a combination of freeze-drying sample preparation technology and analytical electron microscopy to study micro / nano material-liquid interfaces and their interactions from a microscopic perspective. Background Art
[0002] Micro / nano materials have great potential in scientific research and practical applications due to their unique size effects and surface properties. Today, research on such materials and their interfaces with liquids has become an important way to develop new materials and improve the activity and selectivity of materials. For example, by adjusting the hydrophilicity and charge properties of the surface of micro / nano materials, the interaction between the material and the liquid can be controlled, thereby realizing the functional application of the material in a specific environment. Therefore, a deep understanding of the characteristics of the micro / nano material-liquid interface can not only promote the development of related scientific theories, but also lay a solid foundation for practical applications.
[0003] At present, a variety of characterization methods have been widely used in the study of micro / nanomaterial-liquid interfaces. For example, infrared absorption spectroscopy analyzes the molecular vibration of the interface by measuring light absorption to reveal molecular structure information; X-ray absorption and scattering technology can effectively obtain electronic and structural data of the micro / nanomaterial-liquid interface. Although some characterization methods can reveal the structural details of the chemical composition of the micro / nanomaterial-liquid interface, they cannot provide information on its spatial distribution. Electron microscopy, due to its higher spatial and temporal resolution, can image and characterize the micro / nanomaterial-liquid interface at the micro / nanoscale, and fully understand the interface from a microscopic perspective. For example, in-situ environmental transmission electron microscopy can observe the dynamic changes of micro / nanomaterials and liquids at the interface in real time; cryo-transmission electron microscopy can retain the structural integrity of the micro / nanomaterial-liquid interface to the greatest extent. However, these technologies have high requirements for equipment and sample preparation, and there are many experimental parameters that need to be tried and optimized, resulting in long operation time and relatively limited economic benefits. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an electron microscope characterization method for microscopic research of micro / nano material-liquid interface. By utilizing the low-temperature rapid freezing characteristics of liquid nitrogen, the liquid layer of the micro / nano material-liquid interface is frozen in situ, and then the liquid layer is retained to the greatest extent by freeze drying, thereby overcoming the disadvantage that the analytical electron microscope can only image liquid samples under low-temperature conditions. Under normal temperature conditions, the electron microscope can be used to analyze the dried samples that form the micro / nano material-liquid interface liquid layer, realize interface imaging and three-dimensional reconstruction, and analyze the interface and interaction between micro / nano materials and liquids more efficiently and intuitively.
[0005] The object of the present invention is to provide an electron microscope characterization method for microscopically studying a micro / nano material-liquid interface, comprising the following steps:
[0006] (1) Dispersing the micro / nano material in a dispersant by ultrasonication to obtain a suspension, and dropping a few drops of the suspension onto a carrier mesh to obtain a carrier mesh containing the micro / nano material;
[0007] (2) clamping the edge of the grid obtained in step (1) with tweezers, and then dropping the target liquid to form a micro / nano material-liquid interface liquid layer;
[0008] (3) placing the grid obtained in step (2) into a container containing liquid nitrogen for rapid freezing;
[0009] (4) transferring the vessel obtained in step (3) to a freeze dryer;
[0010] (5) transferring the dried carrier mesh in the vessel obtained in step (4) and forming a micro / nano material-liquid interface liquid layer into an electron microscope sample holder, inserting the electron microscope sample holder into an analytical electron microscope, and using the analytical electron microscope to characterize the micro / nano material-liquid interface;
[0011] (6) Use the scanning transmission mode of the analytical electron microscope to perform chemical contrast imaging, use the transmission mode of the analytical electron microscope to characterize the interface microstructure, use the energy scattering spectrum to analyze the distribution of interface elements, and collect electron tomography images of the interface structure by rotating the sample rod.
[0012] In one embodiment of the present invention, in step (1), the dispersant is methanol or ethanol.
[0013] In one embodiment of the present invention, in step (1), the concentration of the suspension is 50-200 g / L. For example, it can be 50 g / L, 100 g / L, 150 g / L, 200 g / L, etc., or any interval value between any two values. Preferably, the concentration of the suspension is 100 g / L.
[0014] In one embodiment of the present invention, in step (1), the ultrasonic dispersion time does not exceed 30 s, and the ultrasonic power of the ultrasonic instrument cannot be greater than 40 kHz.
[0015] In one embodiment of the present invention, in step (1), the carrier mesh is a metal carrier mesh with a support film, such as a copper mesh or a gold mesh.
[0016] In one embodiment of the present invention, in step (2), the target liquid volume is 3-6 μL, illustratively, it can be 3 μL, 4 μL, 5 μL, 6 μL, etc., or any interval value between any two values, preferably, the suspension drop volume is 4 μL; the residence time on the grid is 60-120 s, illustratively, it can be 60 s, 80 s, 100 s, 120 s, etc., or any interval value between any two values, preferably, the residence time on the grid is 120 s; the visually visible state of the target liquid on the grid is a droplet or a small amount of liquid.
[0017] In one embodiment of the present invention, in step (3), the vessel is any vessel that can withstand the low temperature of liquid nitrogen, such as a glass container beaker or a culture dish.
[0018] In one embodiment of the present invention, in step (3), the container needs to be pre-cooled with liquid nitrogen until it no longer boils.
[0019] In one embodiment of the present invention, in step (4), the container needs to be sealed with plastic wrap and pierced with small holes before being transferred to the freeze dryer to prevent the carrier mesh from being contaminated.
[0020] In one embodiment of the present invention, in step (4), after the container is transferred to the freeze dryer, a small amount of liquid nitrogen is still required to ensure that the carrier network is in a frozen state.
[0021] In one embodiment of the present invention, in step (4), the freeze-drying time of the container is 10 to 30 minutes, illustratively, it can be 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc., or any interval value between any two values. Preferably, the freeze-drying time is 20 minutes. The freeze-drying time needs to be strictly controlled. Too long a time will lead to over-drying of the sample.
[0022] In one embodiment of the present invention, in step (5), the electron microscope sample rod is determined according to the purpose of electron microscope characterization. If it is necessary to obtain a scanning transmission image, a transmission image, an energy scattering spectrum and an electron energy loss spectrum of the interface, a low background sample rod is generally used; if it is necessary to reconstruct the interface in three dimensions, a three-dimensional reconstruction rod is generally used.
[0023] In one embodiment of the present invention, the micro / nano material is any one of micro / nano metal material, micro / nano non-metal material, micro / nano polymer material, micro / nano composite material and micro / nano biomaterial; the liquid is any one of water and salt solution.
[0024] The above technical solution of the present invention has the following advantages compared with the prior art:
[0025] The present invention proposes a sample preparation and electron microscope analysis method for retaining a special microscopic interface under special conditions of coexistence of micro / nano materials and liquids. It covers the conditions for freeze-drying sample preparation of micro / nano materials and liquid interfaces and the analytical characterization method of micro / nano materials-liquid interfaces and their interactions, and obtains sample preparation conditions with a high applicability. In addition, the interface of micro / nano materials-liquid contact is characterized and analyzed by combining analytical electron microscopy (including scanning transmission electron microscope mode, transmission electron microscope mode, energy scattering spectrum, and electron tomography), thereby analyzing the interface interaction between micro / nano materials and liquids.
[0026] By using the freeze-drying sample preparation method of the present invention, the micro / nano material-liquid interface can be completely preserved, and the success rate is high, the applicability is wide, and it has good application scenarios. By using the electron microscopy characterization method of the present invention, various forms, components and morphological characteristics of micro / nano materials can also be clearly displayed at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments and comparative examples of the present invention in conjunction with the accompanying drawings, wherein:
[0028] Figure 1 is a flow chart of the method for freeze-drying sample preparation to retain the micro / nano material-liquid interface in Example 1;
[0029] Figure 2 is a scanning transmission electron microscope image of the interface of nano zero-valent iron-chloroauric acid solution obtained under an analytical electron microscope using the sample preparation method of Example 1;
[0030] Figure 3 This is a transmission electron microscope image of the interface of nano zero-valent iron-chloroauric acid solution obtained under an analytical electron microscope using the sample preparation method of Example 1;
[0031] Figure 4 This is the energy spectrum element distribution diagram of the interface of nano zero-valent iron-chloroauric acid solution obtained by the sample preparation method of Example 1 under an analytical electron microscope;
[0032] Figure 5 This is the distribution diagram of O, Cl, Au, and Fe elements at the interface of nano zero-valent iron-chloroauric acid solution obtained by the sample preparation method of Example 1 under an analytical electron microscope;
[0033] Figure 6 This is the energy spectrum of the interface of nano zero-valent iron-chloroauric acid solution obtained under an analytical electron microscope using the sample preparation method of Example 1;
[0034] Figure 7 It is a three-dimensional reconstruction of the interface of nano zero-valent iron-chloroauric acid solution obtained by the sample preparation method of Example 1 under an analytical electron microscope;
[0035] Figure 8 The scanning transmission electron microscope image and the transmission electron microscope image of the interface of the nano zero-valent iron-chloroauric acid solution obtained by the sample preparation method of comparative example 1 under an analytical electron microscope are shown;
[0036] Fig. 9 The scanning transmission electron microscope image and the transmission electron microscope image of the interface of the nano zero-valent iron-chloroauric acid solution obtained by the sample preparation method of comparative example 2 under an analytical electron microscope are shown;
[0037] Fig.10 This is a scanning transmission electron microscope image of the interface of the nano manganese dioxide-chloroauric acid solution obtained by the sample preparation method of Example 2 under an analytical electron microscope;
[0038] Fig.11 This is a transmission electron microscope image of the interface of the nano manganese dioxide-chloroauric acid solution obtained under an analytical electron microscope using the sample preparation method of Example 2;
[0039] Fig.12 This is the energy spectrum element distribution diagram of the interface of nano manganese dioxide-chloroauric acid solution obtained by the sample preparation method of Example 2 under an analytical electron microscope;
[0040] Fig.13 This is the distribution diagram of O, Cl, Au, and Mn elements at the interface of the nano-manganese dioxide-chloroauric acid solution obtained by the sample preparation method of Example 2 under an analytical electron microscope;
[0041] Fig.14 This is the energy spectrum of the interface of nano manganese dioxide-chloroauric acid solution obtained by the sample preparation method in Example 2 under an analytical electron microscope. DETAILED DESCRIPTION
[0042] In order to better understand the present invention, the present invention is further described below in conjunction with specific examples and drawings, so that those skilled in the art can better understand the present invention and implement it, but the content of the present invention is not limited to the following examples. The experimental operations described in the following examples are all routine operations unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0043] Example 1
[0044] An electron microscope characterization method for microscopically studying a micro / nano material-liquid interface comprises the following steps:
[0045] (1) Synthesize nano-zero-valent iron by sodium borohydride reduction method; prepare a 100 mg / L HAuCl4 solution with a pH of 6.0.
[0046] (2) Add nano-zero-valent iron to anhydrous ethanol and disperse it ultrasonically for 20 seconds using an ultrasonic instrument (ultrasonic power of 20 kHz) to obtain a 100 g / L nano-zero-valent iron suspension (see the schematic diagram of the operation). Figure 1); add 10 μL of nano zero-valent iron suspension onto a 200-mesh copper grid, and repeat the adding step twice after the anhydrous ethanol evaporates.
[0047] (3) Use special tweezers for electron microscopy to clamp the edge of the copper mesh, then add 4 μL of HAuCl4 solution and wait for 120 s to form an interface liquid layer of nano-zero-valent iron-chloroauric acid solution. During the waiting process, pour liquid nitrogen into the glass culture dish to pre-cool the glass culture dish so that it no longer boils. When the time is close to 120 s, replenish the liquid nitrogen in the glass culture dish for the last time. After 120 s, quickly place the copper mesh in the glass culture dish and carefully remove the tweezers from the glass culture dish; quickly seal the glass culture dish with plastic wrap and rubber band with small holes pierced in advance; transfer the glass culture dish to a freeze dryer and wait for 20 min before taking out the glass culture dish.
[0048] (4) The copper mesh was transferred to the electron microscope sample rod. The low background sample rod was first inserted into the analytical electron microscope. The scanning transmission mode of the analytical electron microscope was used for chemical contrast imaging. The transmission mode of the analytical electron microscope was used for characterization of the interface microstructure. The energy scattering spectrum was used for analysis of the interface element distribution. The three-dimensional reconstruction rod was then inserted into the analytical electron microscope. The interface structure electron tomography image was collected by rotating the three-dimensional reconstruction rod. The rotation range was -55°~55°, and the rotation was 1° each time. Then, ThermoFisher Inspect3D™ software was used. The cross-correlation method was first used for image movement and tilt alignment. Then, the synchronous iterative reconstruction technology was used to iterate the image 40 times to generate a three-dimensional reconstruction model. Finally, the Avzio™ software was used to render the three-dimensional reconstruction model using the threshold segmentation method. Figure 2-Figure 7 );Depend on Figure 2-Figure 7 It can be seen that nano-zero-valent iron has a high-density core and a low-contrast shell of a few nanometers, presenting a chain structure. The entire particle chain is wrapped by a layer of continuous liquid. Compared with the surrounding area, the contrast of the liquid is higher. Nano-gold particles were observed at the interface. It is speculated that nano-zero-valent iron and chloroauric acid generate nano-gold particles through adsorption and reduction reaction at the interface.
[0049] Comparative Example 1
[0050] An electron microscope characterization method for microscopically studying a micro / nano material-liquid interface comprises the following steps:
[0051] (1) Synthesize nano-zero-valent iron by sodium borohydride reduction method; prepare a 100 mg / L HAuCl4 solution with a pH of 6.0.
[0052] (2) Add nano-zero-valent iron to anhydrous ethanol and disperse it ultrasonically for 20 seconds using an ultrasonic instrument (ultrasonic power of 20 kHz) to obtain a 100 g / L nano-zero-valent iron suspension; drop 10 μL of the nano-zero-valent iron suspension on a 200-mesh copper grid, and repeat the dropping step twice after the anhydrous ethanol evaporates.
[0053] (3) Use liquid nitrogen to precool the liquid ethane copper cylinder for 2.5 min, then fill it with gaseous ethane to convert it into liquid ethane to 3 / 4 of the height of the copper cylinder. Use tweezers to clamp the edge of the copper mesh, install the tweezers and copper mesh into the Vitrobot device, draw 4 μL of HAuCl4 solution and drop it onto the copper mesh to form a nano zero-valent iron-chloroauric acid solution interface liquid layer, wait for 120 s, absorb the excess liquid with filter paper (the imprinting force is set to -2, and the imprinting time is set to 1.5 s), quickly immerse the copper mesh in liquid ethane, carefully remove the tweezers and quickly transfer the frozen copper mesh to the sample box, which is stored in liquid nitrogen.
[0054] (4) Use liquid nitrogen to precool the cryotransfer rod. When the temperature reaches -185 °C, transfer the copper mesh to the cryotransfer rod and insert it into the analytical electron microscope. Use the scanning transmission mode of the analytical electron microscope to perform chemical contrast imaging. Use the transmission mode of the analytical electron microscope to characterize the interface microstructure. Figure 8 );Depend on Figure 8 It can be seen that when using the freezing sample preparation technology under low temperature conditions, a phenomenon similar to that in Example 1 was also observed: the nano-zero-valent iron was wrapped by a continuous layer of liquid, and nano-gold particles were also observed at the interface.
[0055] Comparative Example 2
[0056] An electron microscope characterization method for microscopically studying a micro / nano material-liquid interface comprises the following steps:
[0057] (1) Synthesize nano-zero-valent iron by sodium borohydride reduction method; prepare a 100 mg / L HAuCl4 solution with a pH of 6.0.
[0058] (2) Add nano-zero-valent iron to anhydrous ethanol and disperse it ultrasonically for 20 seconds using an ultrasonic instrument (ultrasonic power of 20 kHz) to obtain a 100 g / L nano-zero-valent iron suspension; drop 10 μL of the nano-zero-valent iron suspension on a 200-mesh copper grid, and repeat the dropping step twice after the anhydrous ethanol evaporates.
[0059] (3) Use special tweezers for electron microscopy to clamp the edge of the copper mesh, then add 4 μL of HAuCl4 solution and wait for 120 s to form an interface liquid layer of nano-zero-valent iron-chloroauric acid solution. During the waiting process, pour liquid nitrogen into the glass culture dish to pre-cool the glass culture dish so that it no longer boils. When the time is almost 120 s, replenish the liquid nitrogen in the glass culture dish for the last time. After 120 s, quickly place the copper mesh in the glass culture dish and carefully remove the tweezers from the glass culture dish; quickly seal the glass culture dish with plastic wrap and rubber band with small holes pierced in advance; transfer the glass culture dish to a freeze dryer and wait for 40 min before taking out the glass culture dish.
[0060] (4) Transfer the grid in the culture dish to the low-background sample holder, then insert the low-background sample holder into the analytical electron microscope, use the scanning transmission mode of the analytical electron microscope to perform chemical contrast imaging, and use the transmission mode of the analytical electron microscope to characterize the interface microstructure ( Fig. 9 ); The results show that due to the long freeze-drying time of the copper mesh, only a partial micro-liquid layer can be observed at the interface. Therefore, the freeze-drying time needs to be strictly controlled when using the sample preparation method proposed in the present invention to characterize the micro / nano material-liquid interface.
[0061] Example 2
[0062] An electron microscope characterization method for microscopically studying a micro / nano material-liquid interface comprises the following steps:
[0063] (1) Prepare a 100 mg / L HAuCl4 solution at a pH of 6.0.
[0064] (2) Add nano-manganese dioxide to anhydrous ethanol and ultrasonically disperse it for 20 s using an ultrasonic instrument (ultrasonic power of 20 kHz) to obtain a 100 g / L nano-manganese dioxide suspension; drop 10 μL of the nano-manganese dioxide suspension on a 200-mesh copper grid, and repeat the dropping step twice after the anhydrous ethanol evaporates.
[0065] (3) Use special tweezers for electron microscopy to clamp the edge of the copper mesh, then add 4 μL of HAuCl4 solution and wait for 120 s to form an interface liquid layer of nano-manganese dioxide-chloroauric acid solution. During the waiting process, pour liquid nitrogen into the glass culture dish to pre-cool the glass culture dish so that it no longer boils. When the time is close to 120 s, replenish the liquid nitrogen in the glass culture dish for the last time. After 120 s, quickly put the copper mesh into the glass culture dish and carefully remove the tweezers from the glass culture dish; quickly seal the glass culture dish with plastic wrap and rubber band with small holes pierced in advance; transfer the glass culture dish to a freeze dryer and wait for 20 min before taking out the glass culture dish.
[0066] (4) Transfer the copper mesh in the culture dish to the low-background sample rod, then insert the low-background sample rod into the analytical electron microscope, use the scanning transmission mode of the analytical electron microscope to perform chemical contrast imaging, use the transmission mode of the analytical electron microscope to characterize the interface microstructure, and use the energy scattering spectrum to analyze the interface element distribution ( Figure 10-Figure 14 );Depend on Figure 10-Figure 14 It can be seen that nano-manganese dioxide has a flaky structure, multiple nano-manganese dioxides are clustered together, and the surface is also wrapped by a layer of continuous liquid. Compared with the surrounding, the contrast of the liquid is higher. Nano-gold particles are also observed at the interface and on the surface of nano-manganese dioxide.
[0067] Obviously, the above embodiments and comparative examples are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. An electron microscopic characterization method for microscopic study of micro / nano material-liquid interface, characterized in that: The following steps are involved: (1) Dispersing the micro / nano material in a dispersant by ultrasonication to obtain a suspension, and dropping a few drops of the suspension onto a carrier mesh to obtain a carrier mesh containing the micro / nano material; (2) Clamping the edge of the carrier grid in step (1) with tweezers, then dropping the target liquid to form a micro / nano material-liquid interface liquid layer, and placing the carrier grid in a container containing liquid nitrogen for freezing; (3) The vessel containing the grid in step (2) is transferred to a freeze dryer for freeze drying; then, the grid which has been dried and formed into a micro / nano material-liquid interface liquid layer is transferred to an electron microscope sample rod at room temperature, and then inserted into an analytical electron microscope; (4) Use the scanning transmission mode of the analytical electron microscope to image the chemical contrast, use the transmission mode of the analytical electron microscope to characterize the interface microstructure, use the energy scattering spectrum to analyze the distribution of interface elements, and collect electron tomography images of the interface structure by rotating the sample rod.
2. The electron microscope characterization method for microscopic study of micro / nano material-liquid interface according to claim 1, characterized in that: In step (1), the dispersant is methanol or ethanol.
3. The electron microscope characterization method for microscopic study of micro / nano material-liquid interface according to claim 1, characterized in that: In step (1), the concentration of the suspension is 50-200 g / L.
4. The electron microscope characterization method for microscopic study of micro / nano material-liquid interface according to claim 1, characterized in that: In step (1), the carrier mesh is a metal carrier mesh with a supporting film.
5. The electron microscope characterization method for microscopic study of micro / nano material-liquid interface according to claim 1, characterized in that: In step (2), the volume of the target liquid is 3-6 μL, the residence time on the grid is 60-120 s, and the visually visible state of the target liquid on the grid is droplets or liquid.
6. The electron microscope characterization method for microscopic study of micro / nano material-liquid interface according to claim 1, characterized in that: In step (3), when the container is transferred to the freeze dryer, liquid nitrogen is still used to ensure that the grid is in a frozen state.
7. The electron microscope characterization method for microscopic study of micro / nano material-liquid interface according to claim 1, characterized in that: In step (3), the freeze-drying time of the container is 15 to 30 minutes.
8. The electron microscope characterization method for microscopic study of micro / nano material-liquid interface according to claim 1, characterized in that: In step (3), the electron microscope sample rod is determined according to the purpose of electron microscope characterization. If it is necessary to obtain a scanning transmission image, a transmission image, an energy scattering spectrum and an electron energy loss spectrum of the interface, a low background sample rod is used; if it is necessary to reconstruct the interface in three dimensions, a three-dimensional reconstruction rod is used.
Citation Information
Patent Citations
Preparation method of heterogeneous interface material sample for electron microscope observation
CN105865869A
Electron microscope characterization method for analyzing interface structure and interaction of organic-inorganic materials
CN118150601A